PENGARUH PENGGANTIAN TEPUNG IKAN DENGAN SUSU AFKIR DALAM RANSUM TERHADAP PERFORMA PRODUKSI DAN KECERNAAN NUTRIEN AYAM BURAS JANTAN - M. E. D, PERTIWI; MASTIKA, I M.; NURIYASA, I M. NURIYASA** (Majalah Ilmiah Peternakan; Vol 20 No 3 (2017): Vol 20, No 3 (2017)DO - 10.24843/MIP.2017.v20.i03.p07, 2017)
The purpose of this study is to determine the effect of fish meal substitution with expired milk in diets on the productivity of cockerels at the age of 2-10 weeks. This study was carried out in Puger Village, Jember Regency, East Java. A Completely Randomized Design (CRD) was used with five treatments and five replicates. Totally, there were 25 experimental units and each unit consists of four cockerels fed without fish meal (R0); 25% diets of fish meal substitution with expired milk (R1); 50% diets of fish meal substitution with expired milk (R2); 75% diets of fish meal substitution with expired milk (R3) and 100% diets of fish meal substitution with expired milk (R4). Diets and water were given ad libitum. The variables observed were performance and nutrient digestibility. It showed that cockerels fed 75% diets of fish meal substitution with expired milk (R3) produced higher final body weight and nutrient digestibility (P<0.05) compared to treatment R0, R1, R2 and R4. Treatment R3 produced 75.08% digestibility coefficient of dry ingredient and 72,21% digestibility coefficient of crude protein. It can be concluded that 75% fish meal substitution with expired milk produced better performance and nutrient digestibility compared to other treatment.